Religious issues and Islamic thought in contemporary world: a few reflections - Ali, Mohd Mumtaz (2019)
This paper intends to address some of the issues which are generally associated to religion especially to Islam such as the issues of radicalism, fundamentalism, terrorism, traditionalism and Islamic thought. It is generally claimed by Western authors that due to the misinterpretation of texts of Islam and negligence of the proper context and improper reading of modernity by Islamic scholars Muslims are subject to radicalism and fundamentalism. The aim of this paper is to ascertain the validity of these claims. It is suggested here that the emergence of radicalism and terrorism are only the symptoms of some other root problems. It is a qualitative research. To analyse the data the critical and analytical method is used.